System based phosphorus management improved the productivity, profitability and nutrient uptake of rainfed rice (Oryza sativa L.) - greengram (Vigna radiata L.) cropping system - Rath, Haramohan; Panda, BB; Verma, AK; Nayak, AK; Jena, J (ORYZA-An International Journal of Rice, 2022)
The effect of system based phosphorus management on crop productivity, profitability and nutrient uptake of rainfed rice-greengram cropping system was studied under medium land situation at ICAR-NRRI, Cuttack, Odisha. The experiment was carried out in both kharif and rabi season of the years 2019-20 and 2020-21. The experiment was laid out in a split plot design with four nutrient management practices in rice viz. recommended dose of fertilizer (RDF), RDF + 25% additional phosphorus(P) through FYM, RDF + 25% additional phosphorus(P) through fertilizer and 75% of RDF (RDF75) in main plots and five nutrient management practices in greengram viz. Control, RDF, RDF + PSB inoculation (RDF+ PSB), RDF + Foliar spray of 2% DAP (RDF + FS) and RDF + PSB inoculation + Foliar spray of 2% DAP (RDF + PSB + FS) in subplots and replicated thrice. Effect of system based phosphorus management had significant effect on productivity, profitability and nutrient uptake by the system. Application of 25 % additional phosphorous to rice through fertilizer improved the rice equivalent yield (REY) and P uptake of the rice - greengram system by 6.6 and 7.1% compared to the application of recommended dose of phosphorus to rice. The same treatment also resulted in significantly highest net returns and B:C ratio from the cropping system compared to all other treatments including application of 25% additional phosphorus through FYM. However, application of PSB and foliar spray of 2% DAP along with recommended dose of phosphorus to greengram improved the REY and P uptake of the system to the tune of 23.4 and 21.3%, respectively, compared to non fertilized plots where as 6.2 and 9.6%, respectively, over recommended dose of P to greengram with highest net return and B:C ratio. Further, application of 25% additional phosphorus through FYM or fertilizer along with RDF to rice followed by application of PSB and foliar spray of 2% DAP along with RDF to greengram produced the highest grain and straw yield, nutrient uptake, gross return, net return and B:C ratio.